Micro- to Nanoscale Morphologies and Chemical Components of Soils Investigated by SEM-EDS for Forensic Science - Yingzi Liu; Yumei Li; Qiang Li; Jie Bao; Dakui Hao; Zhiwen Zhao; Dongxue Song; Jiajia Wang; Zhiheng Hu (Journal of Chemistry)
As a kind of microscale physical evidence, soil can provide significant assistance to forensic science. In this study, soil samples that were collected from eighteen different regions of Shandong Province, China, were examined by scanning electron microscope-energy dispersive spectrometer (SEM-EDS). The homogeneities and diameters of the samples were evaluated by SEM which has been applied to observe objects at nanoscale. The soil from Jiaxiang, a city in Eastern Shandong Province, showed the maximal particle diameter and the sample from Liaocheng, another Eastern city in Shandong Province, showed the best homogeneity. The mass fraction and molar percentages of nine inorganic elements in all samples were analyzed by EDS. Oxygen and silicon showed the highest content in all of these samples. However, different samples exhibited their own characteristic elements, which can help to discriminate them from other samples. In this regard, SEM-EDS-based homogeneity and element analysis might be used as a fast and reliable technique for the soil criminological analysis in Shandong Province.